(untitled) (Economics and region, 2018)
In addition to classical factors of economic growth, which include capital (investments) and neoclassical factors (technologies, innovations, entrepreneurial skills), in today’s conditions, the level of corruption in the country becomes crucial for the effective use of the first two groups of factors. If for developed countries corruption is considered even as a “grease the wheel” effect, then in the main countries, especially in emerging countries, it still has “sand the wheel” effect like a destructive social institution that limits economic development. The article analyzes the dynamics of the level of corruption in Ukraine compared to those countries with which there has often been a matching of the corruption perception index. This dynamic for 2003 - 2017 turned out to be multivectoral, but with a general trend to increase transparency. However, raising the level of transparency does not show a close connection with the dynamics of welfare growth or the growth of net foreign direct investment, as opposed to Bolivia and Vietnam, where this link is rather tight. The level of corruption in Ukraine coincides with the level of corruption in low income countries per capita, which indicates a very low level of public administration in the field of finance, and in general, the performance of state officials by their functions.